Implementasi Pendidikan Karakter (Studi Kasus Penerapan Kurikulum Sekolah Alam Bengawan Solo) - Nugraheni, Hana Navi (2016)
The purpose of this study: 1) to describe the planning, implementation, and evaluation character education contained in the of curriculum of Sekolah Alam Bengawan Solo . 2) to describe the characters developed in the curriculum of Sekolah Bengawan Solo. 3) to describe the role of the curriculum of Sekolah Alam Bengawan Solo to build character education. This study is a qualitative study using an case study design. The technique of collecting data through observation, interviews and documentation. Data validity is tested by triangulation.data analysis technique with an interactive model. The results of this study are: 1) the Sekolah Alam Bengawan Solo has implemented character education that is contained in the curriculum of Sekolah Alam Bengawan Solo. 2) The planning, enforcement, and evaluation of character education in the curriculum of Sekolah Alam Bengawan Solo is integrated in teaching and learning activities, strategy; and learning methods include classroom management; and students, the learning process, learning programs, and extracurricular activities. 3) The character education at the curriculum, developed five main characters are: the love of truth, patience, affection, social instinct and love of each other. 4) The Curriculum of Sekolah Alam Bengawan Solo has an important role to build of students character. Keywords: Character Education, Curriculum